Diversity of insect in immature oil palm plantation in Felcra Seri Mendapat (Paya Jenuang region) / Nur Habibah Ar Azmi - Ar Azmi, Nur Habibah (Faculty of Plantation and Agrotechnology, 2019)
The diversity, evenness of insect in different immature oil palm plot and comparison of population of insect using different trapping method were conducted at Felcra Seri Mendapat (Paya Jenuang Region). The diversity of insect was evaluated in the different oil palm plot because the oil palm plot was divided by trench, thus, obstacles can be avoided. The trapping method that have been used in this case study are sweep nets, yellow pan traps and yellow sticky traps. Samplings were conducted for six weeks starting from August 2018 until September 2018. The total of 3,364 individuals, belonging to six orders and 18 families were capture by using yellow sticky traps whereas, a total of 1,492 individuals belonging to seven orders and 23 families were captured by using yellow pan traps and a total of 2,577 individuals belonging to seven orders and 25 families were capture by using sweep net. The traps were place randomly in the three-different oil palm plot. The trapping method that capture the highest individuals` insect is yellow sticky traps followed by sweep net and yellow pan traps. There are significant different between trapping method and the total individuals of insect captured (p<0.05) through ANOVA analysis. Second oil palm plot has highest Shannon- Weiner Diversity Index followed by first plot and third plot. But some of the families captured in the plot are pest to oil palm. Thus, the organization should apply many management practices to control the pest, yet in the same time the practices can conserve the environment.